Catheter ablation in combined procedures is associated with residual leaks - Zhu, Xuefeng; Li, Wenjing; Chu, Hongxia; Zhong, Lin; Wang, Chunxiao; Li, Jianping; Liang, Pingping; Wang, Lihong; Shi, Lei (Frontiers in Cardiovascular Medicine, 2023)
Objectives To compare patients with atrial fibrillation (AF) undergoing left atrial appendage closure (LAAC) with catheter ablation (CA) and those without CA. Background The CA of AF may cause ridge edema, which may affect the safety of LAAC. Methods Patients with AF (N = 98) who underwent LAAC (combined CA + LAAC procedure group; N = 51) or alone (LAAC group; N = 47) received pre-procedural, intra-procedural, and 6 week post-procedural transesophageal echocardiography (TEE). The depth and ostial diameter of LAA, device compression, residual leak, and ridge thickness were evaluated in the patients who had undergone combined and alone procedures, as well as images of LAA and primary clinical characteristics. Results A residual leak was identified in 27 patients at 6 weeks after implantation by TEE (19 in the combined procedures group and eight in the alone group; p = 0.04). The combined procedure group had a significantly higher rate of a new residual leak than the alone group (25.5 vs. 8.5%; p = 0.03). Meanwhile, compared with at the time of implant, a smaller amount of device compression ratio was significant after 6 weeks (22.44 ± 3.90 vs. 19.59 ± 5.39; p = 0.03). There was no significant difference between both groups in all-cause mortality, cardiovascular mortality, and TIA/stroke/system embolism. Conclusion The combined procedures of CA and LAAC for AF are feasible and safe; however, during the follow-up period, we found that the resolution of ridge edema caused by CA might cause an increased residual leak and a smaller device compression ratio.